Brentuximab Vedotin Treatment for Primary Refractory Hodgkin Lymphoma - Hung-Bo Wu; Shyh-An Yeh; Huei-Yung Chen (Case Reports in Hematology)
Up to 40% of patients with advanced Hodgkin lymphoma (HL) become refractory or relapsed after current standard chemotherapy, among which primary refractory HL confers a particularly poor outcome. With intensive salvage chemotherapy and autologous stem cell transplantation, the long-term remission rate for these patients was only 30%, but more selective treatments with higher therapeutic index are needed. We report the experience of using a new anti-CD30 immunotoxin, brentuximab vedotin, in salvage treatment of a 30-year-old woman with primary refractory Hodgkin lymphoma. The patient presented with SVC syndrome due to the bulky mediastinal tumor and was confirmed to have classical Hodgkin lymphoma, nodular sclerosis type, stage IIIA. The tumor responded to induction chemotherapy transiently, but local progression was noted during subsequent cycles of treatment. Salvage radiotherapy to the mediastinal tumor, obtained no remission but was followed by rapid in-field progression and then lung metastasis. She declined stem cell transplantation and received salvage brentuximab vedotin (BV) therapy, which induced dramatic shrinkage of tumor without significant side effects. Serial followup of PET/CT imaging confirmed a rapid and continuous complete remission for 12 months. Although durability of the remission needs further observation, this case illustrates the excellent efficacy of brentuximab vedotin in primary refractory Hodgkin lymphoma.